Measurement of associated Z plus charm production in proton-proton collisions at root s=8TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Verlag, 2018)
A study of the associated production of a Z boson and a charm quark jet (Z + c), and a comparison to production with a b quark jet (Z + b), in pp collisions at a centre-of-mass energy of 8 TeV are presented. The analysis uses a data sample corresponding to an integrated luminosity of 19.7 fb−1, collected with the CMS detector at the CERN LHC. The Z boson candidates are identified through their decays into pairs of electrons or muons. Jets originating from heavy flavour quarks are identified using semileptonic decays of c or b flavoured hadrons and hadronic decays of charm hadrons. The measurements are performed in the kinematic region with two leptons with p T > 20 GeV, |η| < 2.1, 71 < m < 111 GeV, and heavy flavour jets with p jet T > 25 GeV and |ηjet| < 2.5. The Z + c production cross section is measured to be σ (pp → Z + c + X)B(Z → +−) = 8.8±0.5 (stat)±0.6 (syst) pb. The ratio of the Z+c and Z+b production cross sections is measured to be σ (pp → Z+c+X)/σ (pp → Z+b+X) = 2.0±0.2 (stat)±0.2 (syst). The Z+c production cross section and the cross section ratio are also measured as a function of the transverse momentum of the Z boson and of the heavy flavour jet. The measurements are compared with theoretical predictions.